Global Connectivity of Southern Ocean Ecosystems - Murphy, Eugene J.; Johnston, Nadine M.; Hofmann, Eileen E.; Phillips, Richard A.; Jackson, Jennifer A.; Constable, Andrew J.; Henley, Sian F.; Melbourne-Thomas, Jessica; Trebilco, Rowan; Cavanagh, Rachel D.; Tarling, Geraint A.; Saunders, Ryan A.; et al. (Frontiers in Ecology and Evolution, 2021)
Southern Ocean ecosystems are globally important. Processes in the Antarctic atmosphere, cryosphere, and the Southern Ocean directly influence global atmospheric and oceanic systems. Southern Ocean biogeochemistry has also been shown to have global importance. In contrast, ocean ecological processes are often seen as largely separate from the rest of the global system. In this paper, we consider the degree of ecological connectivity at different trophic levels, linking Southern Ocean ecosystems with the global ocean, and their importance not only for the regional ecosystem but also the wider Earth system. We also consider the human system connections, including the role of Southern Ocean ecosystems in supporting society, culture, and economy in many nations, influencing public and political views and hence policy. Rather than Southern Ocean ecosystems being defined by barriers at particular oceanic fronts, ecological changes are gradual due to cross-front exchanges involving oceanographic processes and organism movement. Millions of seabirds and hundreds of thousands of cetaceans move north out of polar waters in the austral autumn interacting in food webs across the Southern Hemisphere, and a few species cross the equator. A number of species migrate into the east and west ocean-basin boundary current and continental shelf regions of the major southern continents. Human travel in and out of the Southern Ocean region includes fisheries, tourism, and scientific vessels in all ocean sectors. These operations arise from many nations, particularly in the Northern Hemisphere, and are important in local communities as well as national economic, scientific, and political activities. As a result of the extensive connectivity, future changes in Southern Ocean ecosystems will have consequences throughout the Earth system, affecting ecosystem services with socio-economic impacts throughout the world. The high level of connectivity also means that changes and policy decisions in marine ecosystems outside the Southern Ocean have consequences for ecosystems south of the Antarctic Polar Front. Knowledge of Southern Ocean ecosystems and their global connectivity is critical for interpreting current change, projecting future change impacts, and identifying integrated strategies for conserving and managing both the Southern Ocean and the broader Earth system.